Diabetic Neuropathy: A narrative review of pathophysiology, diagnosis, and treatment - Jiménez-Castillo, Gilberto A. (2023)
Diabetic neuropathy occurs in up to 60% of diabetic patients. Diabetic peripheral neuropathy is the most common cause of neuropathy in the world. The pathophysiology of diabetic neuropathy involves peripheral nerve damage due to the accumulation of toxic products derived from hyperglycemia. The central nervous system is subsequently involved through sensitization, decreased function of the inhibitory system, and increased excitability of the facilitative system. The most common symptoms manifest symmetrically, affecting small and large sensory fibers, although atypical forms of presentation have been found. Confirmatory diagnostic tests are reserved for diagnostic doubt, atypical symptoms, or research. The consensus regarding treatment is the prescription of gabapentinoids, tricyclic antidepressants, and serotonin and norepinephrine reuptake inhibitors. These three families are considered the first line.